Comparative Study and Survey on Copy Move Image Forgery Detection Approaches - Naincy,; Bathla, Ashok Kumar (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Nowadays the demand of digital images in various application areas is increasing and thus it is becoming important to ensure the authenticity of images. Due to easy availability of various image editing tools, continuous manipulations are done to create fake or forged images. Although various techniques like copy-move, splicing, resampling etc. for image forgery are present but copy move image forgery has received significant attention these days. Thus the focus of this paper is on copy-move image forgery detection techniques. We have presented a review of commonly used copy move image forgery detection techniques and the comparison of same is also showed to evaluate their performance on basis of various parameters.